2017
DOI: 10.1111/jfb.13278
|View full text |Cite
|
Sign up to set email alerts
|

International survey on the use and welfare of zebrafish Danio rerio in research

Abstract: A survey was conducted regarding zebrafish Danio rerio use for scientific research with a focus on: anaesthesia and euthanasia; housing and husbandry; breeding and production; refinement opportunities. A total of 98 survey responses were received from laboratories in 22 countries in Europe, North America, South America, Asia and Australia. There appears a clear and urgent need to identify the most humane methods of anaesthesia and euthanasia. Aversive responses to MS-222 were widely observed raising concerns a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
97
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 33 publications
3
97
0
3
Order By: Relevance
“…Alternatively, the D. rerio in our study, unlike the G. aculeatus , were captive‐bred, had been used in a previous experiment (Jones et al ., ) and may behave differently to wild fish, particularly in response to stressors such as handling and movement between tanks (Huntingford, ). Moreover, captive‐bred fish may be less affected by standard laboratory lighting than wild‐caught fish, since they were raised with it (Villamizar et al ., ), although it can still be a major source of stress (Lidster et al ., ; Morgan & Tromborg, ). While our study found no apparent value to either form of shelter enrichment, even indicating that D. rerio may actively avoid shade or plants, it was relatively short‐term; longer periods of exposure to enrichment (gravel–plants) in D. rerio do show benefits in terms of both survivorship and female body condition (Lee et al ., ).…”
Section: Ethical Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the D. rerio in our study, unlike the G. aculeatus , were captive‐bred, had been used in a previous experiment (Jones et al ., ) and may behave differently to wild fish, particularly in response to stressors such as handling and movement between tanks (Huntingford, ). Moreover, captive‐bred fish may be less affected by standard laboratory lighting than wild‐caught fish, since they were raised with it (Villamizar et al ., ), although it can still be a major source of stress (Lidster et al ., ; Morgan & Tromborg, ). While our study found no apparent value to either form of shelter enrichment, even indicating that D. rerio may actively avoid shade or plants, it was relatively short‐term; longer periods of exposure to enrichment (gravel–plants) in D. rerio do show benefits in terms of both survivorship and female body condition (Lee et al ., ).…”
Section: Ethical Statementmentioning
confidence: 99%
“…Environmental enrichment, both as a term and in practice, can take many forms and is often applied vaguely or inconsistently across studies -even within a well-studied species such as the zebrafish (Lawrence, 2007;Lidster et al, 2017). It should also be noted that enrichment preferences may vary between species (Kistler et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of enrichment to tanks is often done to improve welfare, but the evidence that environmental enrichment promotes welfare in fishes is controversial, with many effects being species‐specific (Kistler et al ., ). In a recent survey of D. rerio facilities, less than 25% of facilities used environmental enrichment in the form of plants or substrate and were not considered practical by many of the laboratories surveyed (Lidster et al ., ). Motivational and preference tests are often used and can indicate if a species values the presence of enrichment (Sullivan et al ., ).…”
Section: Holding Fishes In the Laboratorymentioning
confidence: 99%
“…Many environmental factors, however, can potentially affect an animal's physiology or behaviour (Killen et al ., ) and so influence research results. In addition, some forms of enrichment, such as the addition of plants and gravel, are considered impractical or costly by some laboratories (Lidster et al ., ) and, importantly, there are no studies describing the duration of benefit imparted by the addition of these physical items for fish and how they should be managed day to day with other husbandry practices. There is unquestionably the need for enrichment approaches that provide measurable welfare benefits without compromising research results.…”
mentioning
confidence: 99%